Evaluating Consumers Perceived Value of Urban Boutique Hotel Uniqueness Towards Willingness to Purchase Intention Case Study: ARTOTEL Jakarta - Aretta, Devi Dianty; Hudrasyah, Herry (Journal of Business and Management, 2014)
The purpose of this research is to evaluate consumer’s perceived value of urban hotel uniqueness toward purchase intention. Boutique hotel is now competing strictly. They find a way to attract travelers with various ways from promotion, marketing strategy, holiday discount, and recently interior design and art is one of the factors they consider to be an added value. The case study in this research is ARTOTEL, an urban boutique hotel located in the center of Jakarta. ARTOTEL distinguished itself from any other hotel by having its wall hand-painted by Indonesia’s local artists. ARTOTEL wants to be the place for artists to express themselves through hotel elements, this is a good message delivered to the consumer of local artists’ appreciation. Each floor provides different experience as product distinctiveness that lead to create a strong identity. It shows that today, servicescape or physical surrounding plays a big role in consumer’s mind. Distinctiveness is what people seek these days to get away from their routines. Emotional factor and core value also considered as a strong component in consumer’s purchase intention in deciding among product choices.Keywords: marketing, servicescape, hotel uniqueness, boutique hotel